Etiological Spectrum of Obstructive Jaundice: "Our Experience in Two University Hospitals in Yemen" - Al-Bahlooli, Saeed H.; Al-Bahlooli, Mohammed A. H.; Shaban, Mohammed A.; Tantawy, Mohammed I. (Thamar University Journal of Natural & Applied Sciences, 2023)
Background: Obstructive jaundice is a surgical emergency with preoperatively uncertain diagnosis. Its early diagnosis and treatment is important to avoid fatal complications.Objective: to determine the etiology of obstructive jaundice.Patients and methods: The data of patients, who were operated for obstructive jaundice at department of Surgery in Sana'a University Hospital and Thamar University Hospital between January 2004 and December 2008, were prospectively analyzed in relation to the causes of obstructive jaundice. The study included 134 patients (91 females and 43 males). Their ages varied from 8-90 years. Results: Among 9 underlying causes of obstructive jaundice, the common bile duct stones were the most common cause, 68 patients (50.7%). Malignancies of pancreas and hepatobiliary tract came in the second place, 33 patients (24.6%), followed by 13 patients with stenosis of papilla of Vater (9.7%) and benign strictures of extrahepatic biliary ducts, 10 patients (7.4%).Ascaris in common bile duct was found in 3 patients. Mirrizi's syndrome was found in 2 patients. Obstruction due to ruptured hydatid cyst was found in 2 patients. Two patients had amoebic liver abscesses One patient had pancreatic pseudocyst. Conclusion: Obstructive jaundice of Yemeni patients in our series was most often due to common bile duct stones followed by malignancy of pancreas and hepatobiliary tract. Cancer of the pancreas was the most common malignant cause. Rare causes such as ascaris in common bile duct was detected. Cooperation between surgeon and radiologist is highly recommended